Gender and inclusion in the CGIAR Research Program on Water, Land and Ecosystems (WLE): an end of program reflection and evaluation - Joshi, Deepa; Braaten, Y.; Hakhu, Arunima; Pradhan, Rubina; Gallant, Bryce (International Water Management Institute, 2021)
The growing relevance of research on gender and social inclusion in agricultural research for development calls for systemic, transformative change processes. Transformative gender ambitions can stand at odds with personal biases and experiences that shape diverse understandings of gender, institutional values, structures and cultures that tend to reward technological quick-fix solutions, and other practical challenges to ‘doing’ gender on the ground. Very little is known about these challenges. How are these challenges navigated by (relatively small) teams of gender researchers, who are often caught between the demand for tangible fast gains on gender, and the intractable challenges of deep-rooted and complex, intersectional gender inequalities? This was the focus of the CGIAR Research Program on Water, Land and Ecosystems (WLE) End of Program Reflection and Evaluation (EoPRE) to assess how gender and inclusion research is pursued, and the key barriers to knowing and doing gender in eight research projects. Adopting a reflexive, self-analytical feminist approach to evaluation, this EoPRE facilitated eight project teams, diverse and with an uneven focus on gender, to connect the dots between the processes of knowing and doing gender research. A key finding of this evaluation is that the need for change is foremost internal. We need to begin by fixing our personal biases and assumptions, and fixing institutional cultures, values and structures instead of just trying to fix things out there, including fixing poor and marginalized women. A key recommendation is to seek more regular and open conversations across researcher disciplines and hierarchies, and between CGIAR and external partners and stakeholders, including feminist grassroots actors and networks – on what works well (and does not) and why. This would allow us to grasp why we start with different meanings and conceptualizations of gender; how agile we are (or not) in adapting to changes on the ground; and how, through a culture of reflection and learning, we might shift pathways to more transformative change processes in a fast evolving and increasingly unequal world.